DYSTOCIA DUE TO INCOMPLETE CERVICAL DILATATION WITH FETAL HYDROCEPHALUS, BRACHYGNATHISM, CLEFT PALATE AND ANKYLOSIS OF LIMBS IN A SALEM BLACK DOE - M. Periyannan; M. Selvaraju; S. Manokaran; K. Senthilkumar; S.Prakash; M. Palanisamy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A full term pregnant 1 ½ year old Salem Black doe was presented with the history of dystocia. Due to incomplete cervical dilatation by cesarean section hydrocephalic fetus with multiple congenital disorders was delivered and complete recovery of doe was reported after a week.